Cine-Dispositives : Essays in Epistemology Across Media - Tortajada, Maria; Albera, Franȯis, 1948- (Book collections on Project MUSE., 2015)
François Albera and Maria Tortajada are professors in the Department of History and Aesthetics of Film at the Universite de Lausanne in Switzerland and the editors of Cinema Beyond Film: Media Epistemology in the Modern Era.